The History of Technologic Advancements in Urology (Springer International Publishing, 2018)
This text explores the history and development of the many technologies that have led to how we treat contemporary urologic problems. From the development of the cystoscope, the advances in laparoscopy, the birth of the field of endourology, to the era of robotics today, urologists have pushed the envelope in technologic innovation. The editors highlight the development of the cystoscope and the early tools used to treat ureteral stones, the development of ureteroscopy, and the applications of lasers and shock wave lithotripsy in the treatment of urolithiasis. Furthermore, they explore the history of minimally invasive treatments in urologic oncology from the story behind the first laparoscopic nephrectomy, the application of hand-assisted technology to the development of robotics and percutaneous treatment approaches (radiofrequency ablation and cryoablation). As the field of urology continues to evolve, urologists will continue to look to the future with the recent applications of histotripsy and regenerative medicine. This text chronicles the creativity, innovation and discovery of the developments of the instruments that allow to practice urology today, as well as glimpse what the future of urology holds.